An investigation into instant puddings as potential vehicula for drug administration in patients with dysphagia - Vasiljević, Ivana; Turković, Erna; Parojčić, Jelena; Vasiljević, Dragana (Archives of Pharmacy, 2022)
The estimated prevalence of swallowing problems and dysphagia is 22%, particularly among pediatric and geriatric population. The drug administration for these individuals is challenging and efforts are being made to enhance solid dosage forms swallowing. The aim of this work was to characterize inulin-based puddings as potential vehicula for solid dosage forms administration. Three marketed instant puddings were prepared according to instructions provided by the manufacturer (mixing with the appropriate amount of cold milk, without cooking) and characterized regarding pH value, rheological characteristics and textural properties (hardness and adhesiveness). The investigated samples differed in terms of inulin content, as gelling agent (3.3-8%), and aroma (vanilla, chocolate, coco). Generally, samples exhibited comparable characteristics. pH values of prepared puddings ranged from 6.57 to 6.90. Apparent viscosity values, measured at 50 s-1, were 4850-16800 mPas, indicating that puddings belong to class 4 (extremely thick drinks), according to International Dysphagia Diet Standardization Initiative Framework, suitable for patients suffering from advanced dysphagia. Samples’ hardness values ranged from 54.6 mN (coco pudding) to 63.9 mN (chocolate pudding), whereas adhesiveness ranged from 30.26 gs (coco pudding) to 40.64 gs (chocolate pudding), indicating the soft structure and swallowing suitability, without the need for intense chewing. The investigated puddings exhibited suitable characteristics in terms of viscosity and textural properties for patients with advanced dysphagia and represent promising approach as vehicula for solid dosage forms administration in the case of this population.